Effect of salinity on plant growth and mineral constituents of maize (Zea mays) - KARA, SEVKET METIN; KESER, SADUMAN (The Indian Journal of Agricultural Sciences, 2014)
The effect of sodium chloride salinity on plant growth and mineral constituents was studied in 3 cultivars of corn of maize (Zea mays L.) during May-June 1999 at Ordu - Turkey. Corn plants were grown under 5 levels of salinity conditions, 0 mM, 35 mM, 70 mM, 105 mM and 140 mM NaCI. High levels of NaCI caused a considerable reduction in plant height and dry weights of shoot and root. With increasing salinity, uptake of CI by the roots and shoots of the com plants markedly increased up to 105 mM of NaCI and then slightly decreased. Salinity favoured accumulation of Na in the roots, whereas CI accumulation was more pronounced-in the shoots. Increasing NaCI salinity resulted in a progressive absorption of Na in detriment of K, thereby increasing Na ; K ratio and causing an ionic disequilibrium, which possibly suppressed plant growth.